PERANCANGAN SISTEM KENDALI MENIRU BURUNG UNTUK UNMMANED AERIAL VEHICLE BERKONFIGURASI SAYAP TETAP - admin admin; Reo Yudhono; Arfie Armelia Erissonia (Sekolah Tinggi Teknologi Kedirgantaraan, 2018)
Bird is the main inspiration in the development of aircraft. The control mechanism on bird’s wing and tail, with simplification, has been applied to aircraft. Bird has simple yet advance control mechanism. Bird’s wing and tail have ability to morph its shape during the flight, in terms of stabilization and control. In this research, we design a control system mimicking bird control mechanism. Both the control surface and it’s mechanism is design mimicking the them on bird. The control surface on wings are the whole outer part of wing. While the tail can be rotate on 2 axis: longitudinal axis and it’s perpendicular axis. A simulation platform is made to shows how the designed control system’s works, which this control system will be installed to the bird-mimicking UAV airframe later. The components that used in the control system are: battery, autopilot (flight controller), servo, motor controller, motor and receiver. The designed control system has shown good respon to the given control command.